Studies on the Effect of Bagging on Yield and Quality of Mango cv. Himsagar - Ramez, Noorhabeeb; Subba, Susan; Taheri, Mohammad Naser; Alam, Mahabub; Hasan, Md Abu (International Journal of Economic Plants, 2024)
The present experiment was carried out twice in a mango orchard situated in the village of Ghoragacha, Nadia, West Bengal (741 245), India during the months of March to June in the year 2019 and 2020 with twenty-one trees of mango cultivar himsagar comprising seven treatments viz. T1: Non-woven yellow bag, T2: Non-woven red bag, T3: Non-woven Blue bag, T4: Non-woven white bag, T5: Non-woven green bag, T6: Newspaper and T7: Control was laid out in randomized block design with three replication. The result from the present experiment revealed that there were significant variation in fruit weight, fruit length, fruit diameter, fruit volume, fruit peel weight and fruit seed weight. Healthy bearer and productive mango trees were selected and the fruits when at pea stage were considered for bagging. After bagging in a different coloured paper bags and newspaper bags, stapled is done carefully to cover the fruits from the direct sunlight and also to avoid open space for entry of insects or rain, etc. The physical and chemical data were collected from both the year i.e., 2019 and 2020 and an average data were given. The highest fruit weight (256.00 g), highest fruit volume (224.38 ml), highest fruit length (89.68 mm), highest fruit diameter (57.15 cm) and highest fruit peel weight were observed in T5 treatment, where non-woven green bags were used and highest fruit seed weight (57.15 cm) was observed in control. However, there were no such significant changes in terms of chemical properties of fruits.